Investigating The Influence of Halal Certification on Millennials’ Purchase Intention and Brand Loyalty in The Indonesian Food Industry - Ramadhan, Yusuf; Darmawan, Roy; Nasihin, A. Khoirun; Sabani, Nurus (Indonesian Journal of Business and Entrepreneurship, 2024)
Background: Indonesia is a country with the largest Muslim population in the world.The food industry in Indonesia is largely determined by the halal certification issued by the Majelis Ulama Indonesia (MUI). A halal certificate is one of the requirements that must be met for food product entrepreneurs. A halal certificate is a proof that the food product produced has gone through a production and processing process followingIslamic religious requirements.Purpose: This paper aims to provide information on the effect of halal certification on purchasing interests and consumer loyalty in brands that have halal certification on their food products.Design/methodology/approach: The method used in this study is Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) with the AMOS approach. The sampling technique used was purposive sampling.Findings/Result: The results of the study show that the variable halal certification has an influence on purchase intention, and purchase intention has an effect on brand loyalty. The results of this study also provide a view for business actors, especially the food industry in Indonesia, that halal certificates are one of the factors that have a major influence on the existence of the food industry business in the future. Halal certificates not only providebenefits to consumers but also provide benefits to producers to achieve broader target consumers.Conclusion: Halal certification has a significant influence on consumer purchasing intentions in the Indonesian food industry. This certification increases purchasing interest and consumer confidence in product quality, which in turn encourages brand loyalty. In addition, halal certification is important for the sustainability of the food business because it can attract a wider market, providing benefits for consumers and producers. This research also confirms that the halal concept is a business issue based on Islamic law, and encourages the government to continue to socialize halal certification to have a positive impact on the health and economic sectors.Originality/value (State of the art): The findings of this research reveal how halal certification significantly influences purchase intention. This implies that providing halal certificates to food products in Indonesia can increase consumer buying interest because it can provide confidence that the products adhere to halal principles. Additionally, it can enhance consumer confidence in product quality and compliance, leading to repeat purchases, and indicating consumer loyalty to preferred brands.Keywords: halal certification, purchase intention, millennial generation, brand loyalty, structural equation modeling (SEM)